MEMBANGUN KARAKTER BANGSA YANG BERADAB MELALUI BUDAYA KOMUNIKASI (BAHASA INDONESIA) YANG SANTUN: KASUS PADA MEDIA CETAK DI MAKASSAR (Building Well-Mannered Character Through Polite Communication (Indonesian Language): Case Study of Mass Media in Makassar) - Nurlina Arisnawati (SAWERIGADING, 2014)
The writing aims at describing the form of polite communication on case study of mass media language in Makassar including Fajar, Tribun, and Cakrawala. Method used is descriptive qualitative with noting technique. Result of analysis shows that speech contained in the mass media is in two forms of communication, impolite and polite communication. The form of impolite communication is marked by: a) critic is conveyed directly, b) there is emotional drive when speaking, c) the speaker is protective towards his opinion, d) The speaker corners the speaker partner, and e) the spesker accuses the speaker partner based on suspicious; whilst the form of polite communication could be identified by: a) the speaker speaks properly, b) the speaker emphasizes on main topic conveyed, c) the speaker always has good prejudice to speaker partner, d) the speaker is opened and conveys critic in general.